Polycystic Ovarian Condition May Be a Risk Factor for Ovarian Tumor Development in the Laying Hen Model of Spontaneous Ovarian Cancer - Hyun Ju Lee; Janice M. Bahr; Pincas Bitterman; Sanjib Basu; Sameer Sharma; Jacques S. Abramowicz; Animesh Barua (Journal of Immunology Research)
Chronic inflammation and long-standing oxidative stress are potential predisposing factors for developing malignancies, including ovarian cancer (OVCA). Information on the association of ovarian chronic abnormal conditions, including polycystic ovarian syndrome (PCOS), with the development of OVCA is unknown. The goal of this study was to examine if polycystic ovarian conditions are associated with OVCA development. In the exploratory study, 3–4-year-old laying hens were randomly selected and examined for the presence of polycystic ovaries with cancer (PCOC). In the prospective study, hens were monitored by ultrasound scanning to detect the incidence of a polycystic ovaries and subsequent development of OVCA. Tissues from normal ovaries and PCOC were examined for macrophage infiltration, expression of interleukin-16, and superoxide dismutase 2. The exploratory study detected spontaneous PCOC at early and late stages in hens. PCOC in hens were accompanied with influx of macrophages (17.33 ± 2.26 in PCOC at the early stage and 24.24 ± 2.5 in PCOC at the late stage in 20 mm2 areas of tissue as compared with 6.77 ± 1.58 in normal hens). Expression of interleukin-16 was more than 2.5-fold higher and superoxide dismutase 2 was approximately 3-fold higher in PCOC hens than normal hens. The prospective study showed the development of OVCA in some hens with polycystic ovarian condition (PCO). PCOC development in hens was associated with chronic inflammation in the ovary. Laying hens may represent a potential model for the study of spontaneous PCOS and its long-term risk of PCOC development.